2020
DOI: 10.1162/jocn_a_01537
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Amygdala Activity and Phobic Fear through Cognitive Top–Down Regulation

Abstract: The amygdala is critically involved in emotional processing, including fear responses, and shows hyperactivity in anxiety disorders. Previous research in healthy participants has indicated that amygdala activity is down-regulated by cognitively demanding tasks that engage the PFC. It is unknown, however, if such an acute down-regulation of amygdala activity might correlate with reduced fear in anxious participants. In an fMRI study of 43 participants (11 men) with fear of snakes, we found reduced amygdala acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…Such regulation mechanisms through top-down control exerted by the PFC on the amygdala have been reported in humans, during concurrent cognitive and emotional tasks (Loos et al, 2020; for review see Okon-Singer, Hendler, Pessoa, & Shackman, 2015). Consistently, our functional connectivity results suggest that, in our experiment, top-down control on SN regions may have occurred during threat of stressors.…”
Section: Discussionsupporting
confidence: 90%
“…Such regulation mechanisms through top-down control exerted by the PFC on the amygdala have been reported in humans, during concurrent cognitive and emotional tasks (Loos et al, 2020; for review see Okon-Singer, Hendler, Pessoa, & Shackman, 2015). Consistently, our functional connectivity results suggest that, in our experiment, top-down control on SN regions may have occurred during threat of stressors.…”
Section: Discussionsupporting
confidence: 90%
“… 1 , 22 26 ) or performed immediately after repeated memory reactivation (e.g. 29 , 30 , 44 ). In contrast to that, our study employed a single reactivation trial in order to trigger a reconsolidation process instead of extinction 27 , as well as a 10 min wait period in order to accommodate memory destabilisation to take place before the intervention is started 16 19 which is a procedural step in line with various other studies 32 , 33 , 35 , 46 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the amygdala plays a vital role in several different emotional memory processes, such as consolidation and reconsolidation 41 . Furthermore, inhibition of the amygdala is a potential working mechanism through which cognitive demand could enhance extinction 29 , 42 44 . It remains therefore unknown whether a non-emotional working memory task, which has been shown to systematically inhibit the amygdala 43 , can disrupt the reconsolidation of conditioned threat memories (but see 45 for a preprint).…”
Section: Introductionmentioning
confidence: 99%
“…If a cognitively demanding task can reduce threat‐related processes (Carter et al, 2003; Vytal et al, 2012) via downregulation of the amygdala, this may have clinical implications. Indeed, laboratory studies have shown that making cognitively demanding eye movements (de Voogd, Kanen, et al, 2018) or a working memory task (de Voogd & Phelps, 2020; Loos et al, 2020) embedded during extinction learning reduces defensive responses to threat in healthy (de Voogd, Kanen, et al, 2018; de Voogd & Phelps, 2020) and phobic (Loos et al, 2020) participants. These cognitively demanding tasks during extinction learning were accompanied by downregulation of the amygdala (de Voogd, Kanen, et al, 2018; Loos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%